Utilization of drug checking services in Austria: a cross-sectional online survey - Alexandra Karden; Tobias Fragner; Cornelia Feichtinger; Julian Strizek; Daragh T. McDermott; Igor Grabovac (Harm Reduction Journal)
Abstract Background The use of psychoactive substances is a key public health issue due to its impact on mental, physical, and social health. Integrated drug checking is a well-known harm reduction and addiction prevention measure and is currently implemented in four federal states in Austria. The aim of this study is to investigate the prevalence of drug checking use among a web-survey sample of people who use drugs (PWUD) in Austria and to examine differences in socio-demographic and substance use characteristics between individuals with and without drug checking experience. In addition, reasons for not using these services are explored. Methods A secondary data analysis of the Austrian data from the European Web Survey on Drugs (EWSD), a targeted survey conducted between March and May 2021 was performed. Based on reported drug checking experience, the data set was divided into two groups - those with and without drug checking experience – and compared. Results In this web-survey sample of PWUD (n = 1113), 20.1% reported prior use of a drug checking service in Austria. The groups with drug checking experience (n = 224) and those without (n = 889) differed significantly in both univariate and multivariate analyses. Univariate analysis revealed significant differences in terms of age, household composition, highest level of education, employment status, region of residence, substance use prevalences and treatment experience. Participants who used cannabis only had significantly less experience with drug checking. No significant differences were found regarding gender and income. While logistic regression analysis showed a significant relationship between sociodemographic predictors and drug checking experience, this relationship was relatively weak. The main reasons for not having used the services yet included a high level of trust in the source of supply (68%), confidence in receiving high quality of substances (64%), and a lack of service availability near the place of residence (62%). Conclusions The results indicate that drug checking services are well-accepted and trusted but not equally accessed by and accessible to all PWUD. Specifically, people who use only cannabis and those residing with parents or in rural or small-town areas access services less. In conclusion, there is considerable potential for expanding the availability and accessibility of drug checking services in Austria, particularly to reach underserved groups of PWUD who could benefit from this intervention.